2022
DOI: 10.3389/fpsyg.2021.800417
|View full text |Cite
|
Sign up to set email alerts
|

Chinese English as a Foreign Language Teachers’ Job Satisfaction, Resilience, and Their Psychological Well-Being

Abstract: Job satisfaction, resilience, and teacher well-being, as the three major psychological variables emotioncy- based education, have received special attention among English as a foreign language (EFL) researchers. To pursue the line of this inquiry, this particular study aimed to investigate the relationship between Chinese EFL teachers’ job satisfaction, resilience, and their well-being. To conduct the study, 343 Chinese EFL teachers with different academic qualifications, various academic degrees, and differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 66 publications
(85 reference statements)
0
8
0
1
Order By: Relevance
“…Furthermore, the teacher-researchers in our study may have experienced challenges or fluctuations commonly shared by teachers, but of different intensities, echoing Xue's (2021) finding that academic research stimulates teachers to be more responsive and resilient in ever-changing contexts. Concerning contextspecific features, individual teachers' resilience development is understood in their situational cultures and contexts Han, 2022). In the Chinese context, the last two decades have witnessed many educational reforms (Li et al, 2019), bringing uncertainty to frontline teachers and requiring them to enhance their resilience to better cope with difficulties in transforming teaching practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the teacher-researchers in our study may have experienced challenges or fluctuations commonly shared by teachers, but of different intensities, echoing Xue's (2021) finding that academic research stimulates teachers to be more responsive and resilient in ever-changing contexts. Concerning contextspecific features, individual teachers' resilience development is understood in their situational cultures and contexts Han, 2022). In the Chinese context, the last two decades have witnessed many educational reforms (Li et al, 2019), bringing uncertainty to frontline teachers and requiring them to enhance their resilience to better cope with difficulties in transforming teaching practices.…”
Section: Discussionmentioning
confidence: 99%
“…They further concluded that these teachers' capacities to manage challenges vary according to life experiences and events, the strength and conviction of educational ideals, a sense of efficacy and agency, and the support of leaders and colleagues. Numerous recent studies have explored the relationship between teacher resilience and other concepts, such as teaching success (Li and Lv, 2022), job satisfaction and well-being (Han, 2022), and teaching performance in the context of COVID-19 Fokkens-Bruinsma et al, 2023). These studies directly point to the essential role of teacher resilience in teacher development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For a comprehensive understanding of the manifestations of psychological contracts and professional identity, it is crucial to consider the cultural subtleties that are linked with these concepts. This is particularly important when examining these interactions within specific contexts, such as the expanding educational environment in China [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…137 of 2014 concerning National Standards for Early Childhood Education. Improving the quality of learning will be more guaranteed if the pedagogic competence is also good because pedagogic competence is a core competency that can support educational goals (Han, 2022). This is supported by the Regulation of the Minister of Education and Culture Number 137 of 2014 which states that the pedagogic competencies of PAUD teachers that must be mastered are, 1) Analyzing the development of students according to the character of early childhood; 2) Apply playing theory according to aspects of student development; 3) Designing early childhood development activities; 4) Organizing educational development activities; 5) Utilizing technology, information and communication; 6) Developing children's potential; 7) Communicate effectively; 8) Organizing and making reports; 9) Determine the target scope of the assessment; 10) Using the results of the assessment for the benefit of child development; 11) Reflect.…”
Section: Introductionmentioning
confidence: 99%